Factor Analysis of Evacuation Behavior in Various Disaster Scenarios - Tsukamoto, Junya; Fujita, Kaede; Ichikawa, Manabu (Journal of disaster research, 2025)
As a precautionary measure against large-scale earthquakes, it is important to understand evacuation destinations and tendencies in the event of a disaster. However, current damage assumptions regarding evacuees are not necessarily sufficient. In particular, problems such as insufficient evacuee support may arise in municipalities with no experience of large-scale disasters. Therefore, in this study, we analyzed the internal and external factors affecting evacuation behavior during earthquakes through a questionnaire survey. Using choice experiment-type conjoint analysis, we clarified residents’ tendencies across various hypothetical scenarios beyond actual disaster experiences. Notably, people who evacuate by car tend to make that decision before the disaster. Harsh temperature conditions psychologically inhibit going to evacuation shelters, and many residents are sensitive to earthquake damage in mountainous areas. However, evacuation-related factors vary significantly depending on the disaster context and individual perception, suggesting limitations in capturing them clearly from questionnaire surveys. We hope that these findings will contribute to a better understanding of evacuees’ needs and evacuation tendencies in each municipality.